Influ??ncia dos membros do conselho na tomada de decis??o estrat??gica em um grupo empresarial familiar de grande porte - Ribeiro, Ivano (2016)
The boards are seen as a real black box due to knowing little about the influence of its members in organizational decisions. Few studies have addressed this issue in family corporations, either being by the low number of formal councils or the difficulty to access information. This study aimed to answer the following question: what is the influence of the board composition in strategic decision making in a large family corporate group? For this purpose, a content analysis of 38 proceedings and two board meeting transcripts of a large family corporate group was performed. The results indicate that the internal members have a strong focus on operational issues, while the external members are guided in strategic aspects. The existence of two families in the shareholding control creates conflicts, and there is also support for decisions within the family. The members with extensive experience are resistant to change their opinions and avoid decisions involving retrenchment, even facing unfavorable scenarios. The main contributions of this study relate to: identify some theoretical dimensions that involve the study of decision making; evidence to show that conflicts between different families are detrimental to decision making in the board; and indications that the participation of outside directors is critical to increasing the strategic focus of the decisions.